(untitled) (Journal of Dhaka Medical College, 2015)
Cat-scratch disease is an infectious disease caused by Bartonella henselae, a gram-negative bacillus. The disease is usually transmitted to the human being by cat scratches. Cat-scratch disease typically presents with painful regional lymphadenopathy. Systemic involvement is unusual. A 35 years old lady, came with the complaints of fever, abdominal pain along with nausea, anorexia & difficulties of swallowing for 6 months. She has painful cervical lymphadenopathy. Histopathology of her lymph node biopsy shows features of cat-scratch disease. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21550 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 229-231